Nomenclatural changes in a taxonomically complex group (Amphipoda: Gammaridae) - García-París, Mario; Jurado-Angulo, Pilar; Rodríguez-Flores, Paula C.; Rosas-Ramos, Natalia (Zootaxa, 2023)
The family Gammaridae is a large monophyletic group with a complicated taxonomy. A nomenclatural review of the taxonomic status of Pectenogammarus Reid, 1940 was conducted based on Hou & Sket (2016) and Sket & Hou (2018) phylogenetic proposals. These authors used the name Homoeogammarus Schellenberg, 1937 for a set of morphologically diverse taxa previously included mainly within Echinogammarus Stebbing, 1899. Unfortunately, the use of the name Homoeogammarus Schellenberg, 1937 is problematic. As a result of a detailed bibliographic review, we propose the name Pectenogammarus Reid, 1940 (stat. nov.) for the “Homoeogammarus” clade (Sket & Hou 2018), which results in 20 new combinations. In addition, two genera are here formally synonymised as follows: Pectenogammarus Reid, 1940 = Homoeogammarus Barnard et Barnard, 1983, syn. nov. = Laurogammarus G.S. Karaman, 1984, syn. nov. A synonymic catalogue is provided.